Prevalence of Burnout Syndrome and associated factors in medical students under different educational models - Prata,Thiago Santos Corrêa (2021)
SUMMARY OBJECTIVE: The objective of this study was to estimate the current prevalence of burnout syndrome among medical students at the Federal University of Sergipe and identify its associated factors. METHODS: This cross-sectional study was conducted with medical students randomly selected between April and June 2019. This study compared two medical schools from the same university with different teaching models: the Federal University of Sergipe, Aracaju campus, with a traditional teaching model, and the Federal University of Sergipe Lagarto campus, with a problem-based learning teaching model. An online questionnaire on the sociodemographic characteristics, personal aspects, and educational process of the participants, in addition to the Malash Burnout Inventory-Student Survey questionnaire for screening burnout syndrome, was distributed to the participants. The descriptive analysis of the data, calculation of the prevalence ratios, and multivariate analysis by logistic regression were performed. RESULTS: This study included 213 students with an average age of 23±3.77, and 50.2% of the students were male. Among the sample, 21.6% of the students met the three-dimensional criterion for burnout syndrome and 51.6% met the two-dimensional criterion. Burnout levels were higher in the students who rarely received the emotional support they needed in the program (OR 3.98), those who thought about dropping out of the undergraduate (OR 2.88), and those who considered their academic performance to be regular or weak (OR 12.1). The traditional teaching model was not a factor associated with burnout syndrome. CONCLUSIONS: The results suggest that a high prevalence of burnout syndrome is associated with psychosocial factors and the educational processes of medical students.